Growth and mortality of Haemulon plumieri (Perciformes: Haemulidae) in the Los Frailes Archipelago, Venezuela - González, Delvalle; Eslava, Nora; González, Leo Walter; Guevara, Francisco (Revista de Biología Tropical, 2019)
The white grunt Haemulon plumieri is abundant in northeastern Venezuela, but the biological and fishery aspects of this species have been little studied in the country. The objective of this study was to estimate the growth and mortality of this resource. We collected samples monthly from January to December 2014, obtaining 2 967 specimens. Total length (cm) and weight (g) were determined for each specimen. No sexual dimorphism was shown with respect to length (tS = 0.093; P > 0.05). Thus, one length-weight ratio was established for both sexes: W = 1.4×10-3* L2.99, which showed isometric growth. FiSAT package routines were used to estimate the growth parameters of the individual growth model of von Bertalanffy: L∞ = 30.95 cm, k = 0.67/year, W∞ = 418.17 g, t0 = -0.24 years. We estimated an max age of 4 years. The coefficient of variation of the growth performance index (Ø′) for the direct method (CV = 5.26 %) showed a variability in growth patterns according to region. The rate of natural mortality (M = 1.36/year) was high, possibly due to predation and disease, among others. Rates of fishing mortality (F = 1.95/year) and total mortality (Z = 3.31/year) were high. The exploitation rate (E = 0.59/year) indicates that H. plumieri is likely overexploited.